Evolution of red blood cell membrane complement regulatory proteins and rheology in septic patients: An exploratory study - Vanderelst, Julie; Rousseau, Alexandre; Selvais, Nicolas; Biston, Patrick; Zouaoui Boudjeltia, Karim; Piagnerelli, Michaël (Frontiers in Medicine, 2022)
Background During sepsis, red blood cell (RBC) deformability is altered. Persistence of these alterations is associated with poor outcome. Activation of the complement system is enhanced during sepsis and RBCs are protected by membrane surface proteins like CD35, CD55 and CD59. In malaria characterized by severe anemia, a study reported links between the modifications of the expression of these RBCs membrane proteins and erythrophagocytosis. We studied the evolution of RBCs deformability and the expression of RBC membrane surface IgG and regulatory proteins in septic patients. Methods By flow cytometry technics, we measured at ICU admission and at day 3–5, the RBC membrane expression of IgG and complement proteins (CD35, 55, 59) in septic patients compared to RBCs from healthy volunteers. Results were expressed in percentage of RBCs positive for the protein. RBC shape was assessed using Pearson's second coefficient of dissymmetry (PCD) on the histogram obtained with a flow cytometer technique. A null value represents a perfect spherical shape. RBC deformability was determined using ektacytometry by the elongation index in relation to the shear stress (0.3–50 Pa) applied to the RBC membrane. A higher elongation index indicates greater RBC deformability. Results RBCs from 11 septic patients were compared to RBCs from 21 volunteers. At ICU admission, RBCs from septic patients were significantly more spherical and RBC deformability was significantly lower in septic patients for all shear stress ≥1.93 Pa. These alterations of shape and deformability persists at day 3–5. We observed a significant decrease at ICU admission only in CD35 expression on RBCs from septic patients. This low expression remained at day 3–5. Conclusions We observed in RBCs from septic patients a rapid decrease expression of CD35 membrane protein protecting against complement activation. These modifications associated with altered RBC deformability and shape could facilitate erythrophagocytosis, contributing to anemia observed in sepsis. Other studies with a large number of patients and assessment of erythrophagocytosis were needed to confirm these preliminary data.